A STUDY ON THE SENSITIVITY ANALYSIS OF THE HYDRODYNAMIC DERIVATIVES ON THE MANEUVERABILITY OF KVLCC2 IN SHALLOW WATER - Sang-Hyun Kim (Brodogradnja, 2017)
To assess the manoeuvrability of ships in shallow water at the early design stage, reliable simulation models which present shallow water effect are required. However, studies on the manoeuvrability of ship at low speeds in shallow water have been performed less than manoeuvrability in deep water. Also, the limitation of model that the effects of the keel clearance on manoeuvrability are applied to has been validated through previous studies. In this study, the manoeuvrability characteristics of the ship sailing in shallow water at low speed are evaluated by applying the mathematical model considering the shallow water effect. And the sensitivity analysis on shallow water manoeuvring simulation is performed in order to determine hydrodynamic derivatives which are necessary to be derived exactly due to the limitation of the shallow water model used in previous studies. Through this study, it could be confirmed that great importance of estimation of manoeuvrability could be found through the sensitivity index factor of hydrodynamic derivatives changing in the situation operating the shallow water at low speed.